Emergence of Carbapenem- and Tigecycline-Resistant Proteus cibarius of Animal Origin - Li, Yan; Wang, Qian; Peng, Kai; Liu, Yuan; Li, Ruichao; Wang, Zhiqiang (Frontiers in Microbiology, 2020)
Emergence of tet(X) and carbapenemase genes in Enterobacterales poses significant challenges to treatment of infectious diseases. Convergence of these two categories of genes in individual pathogen would deteriorate the AMR crisis furthermore. Here, tigecycline resistant Enterobacterales strains were isolated and detected with carbapenemase genes, characterized by antimicrobial susceptibility testing, PCR, conjugation assay, whole genome sequencing and bioinformatics analysis. Three tigecycline resistant isolates consisting of one plasmid-mediated tet(X4)-bearing Escherichia fergusonii and two chromosomal tet(X6)-bearing Proteus cibarius were recovered from chicken faeces. The tet(X4) was located on a conjugative IncX1 plasmid pHNCF11W-tetX4 encoding the identical structure with reported tet(X4)-bearing IncX1 plasmids in E. coli. Among two P. cibarius strains, tet(X6) was located on two similar chromosomal MDR regions with genetic contexts IS26-aac(3)-IVa-aph(4)-Ia-ISEc59-tnpA-tet(X6)-orf-orf-ISCR2-virD2-floR-ISCR2-glmM -sul2 and IS26-aac(3)-IVa-aph(4)-Ia-ISEc59-tnpA-tet(X6)-orf-orf-ISCR2-glmM-sul2. Apart from tet(X6), P. cibarius HNCF44W harbored a novel transposon Tn6450b positive for blaNDM-1 on a conjugative plasmid. This study probed the genomic basis of three tet(X)-bearing tigecycline resistant strains, one of which coharbored blaNDM-1 and tet(X6), and identified P. cibarius as the important reservoir of tet(X6) variants. Emergence of P. cibarius encoding both blaNDM-1 and tet(X6) reveals a potential public health risk.